Model Implementasi Budaya Religius terhadap Siswa di Sekolah Dasar Negeri Giwangan Yogyakarta - Widia Wahyuniati; Sutarman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Religious culture, namely attitudes and behavior that are obedient in implementing the teachings of the religion one adheres to, tolerance towards parties with different understanding and beliefs, and living in harmony with people of other religions. The research aims to determine the model of student cultural implementation in Giwangan state elementary schools. The research uses qualitative methods and a descriptive approarch. In this research, the data collection techniques used interview, documentation and obsevation techniques. The reserch subjects were for people consisting of the school principal, two Islamic religious educations teachers, and student. Determining subjects used purposive sampling , while data analysis techniques used data collection, data reduction, data presentation, and data conclusion. Based on the research results, it found that teachers create a religious cultural climate through activities to increase hablumminallah in quality and quantity, as well as making the school a religious institution. In addition, there are methods used in the strategy of cultivating religious culture at Giwangan State Elementary School including: knowing, living and religious ativities. Knowing is a method of cultivating religious culture by providing mastery of material on noble moral values. This is implemented by teachers by providing advice and reminding students continuously.